Islamic Legal Perspectives on Refugee Protection and Welfare: A Case Study of Malaysia - Abas, All-Mu'izz; Samuri, Mohd Al Adib (De Jure: Jurnal Hukum dan Syari'ah, 2024)
This article examines the refugee crisis in Malaysia from the perspective of Islamic law, addressing the challenges arising from the absence of a formal legal framework for refugee protection. Through a legal normative approach and in-depth interviews with Islamic authorities and NGOs, this study investigates Islamic principles related to refugee welfare. The findings of this study reveal that Malaysia has an ethical and legal responsibility under Islamic law (domestic and legal normative) to protect and support refugees despite not signing the 1951 Refugee Convention. This study emphasises the potential role of Islamic authorities as part of the government body in administering, coordinating, and implementing Islamic welfare efforts to meet the needs of refugees. By aligning refugee support with Islamic values, Malaysia can improve its ability to provide comprehensive care and protection to refugees, fulfilling religious and humanitarian duties. This integrated approach could serve as a model for other Muslim-majority countries, promoting a more inclusive and compassionate response to the global refugee crisis.